Study of Search Algorithm Optimization from Multi-Version Data Warehouse using NoSQL Non-relational Database - Lutfi Rahmatuti Maghfiroh; Ramadhan Azizulhakim Yusuf (Politeknik Statistika STIS, 2021)
Statistics Indonesia, which produces large-scale data, requires effective and optimal storage. Research related to Multi-Version Data Warehouse (MVDW), which utilizes document-based NoSQL itself, has attempted to be developed for the sake of BPS data storage and proposed an algorithm to store and search data. This paper is made to examine algorithm optimization methods to reduce the time used in the process of storing and searching data when needed. The algorithm proposed in this paper focuses on the data storage process by suggesting a storage model that generalizes the coding of variables in the data warehouse used so that later data searches can be carried out more easily and optimally. Other optimization methods are also carried out by applying query optimization methods to support and improve the optimization of the proposed algorithm. The results of the two optimization methods carried out can be said to be successful because the time used in the data search process by utilizing the algorithm after the application of the optimization method has been reduced when compared to the data search process using algorithms that have been developed by previous research.